Hardy-Sobolev spaces of complex tangential derivatives of holomorphic functions in domains of finite type - Grellier, Sandrine (Mathematica Scandinavica, 2002)
In this paper, we prove Fefferman-Stein like characterizations of Hardy-Sobolev spaces of complex tangential derivatives of holomorphic functions in domains of finite type in C^n. We also study the relationship between these complex tangential Hardy-Sobolev spaces and the usual ones. We also obtain partial results on domains not necessarily of finite type.